The Application of Criminal Sanctions on the Distribution of Alcoholic Drinks - Haris Budiman; Ela Nurlaela; Diding Rahmat; Suwari Akhmaddhian (Faculty of Law, Universitas Sebelas Maret, 2020)
This study aims to investigate the criminal sanctions on the distribution of alcoholic drinks as well as its application based on Regional Regulation. This case study was conducted in Kuningan District by applying juridical empirical research method. The results showed that Kuningan District has Regional Regulation No. 6 of 2014 concerning Supervision and Control of Alcoholic Drinks. This Regional Regulation regulates the distribution and sale of alcoholic drinks which are classified into 3 (three) groups, namely group A, group B, and group C. These three groups of alcoholic drinks can only be sold in star hotels with the Regent’s permission. Law enforcement in the application of criminal sanctions on the distribution of alcoholic drinks is carried out by holding raids in collaboration with related parties which are then followed up by carrying out investigation, search, and confiscation of alcoholic drinks. The sanctions imposed are in the form of imprisonment and/or fines.